Prevention of intrauterine post-surgical adhesions in hysteroscopy. A systematic review. (August 2016) - Di Spiezio Sardo, Attilio; Calagna, Gloria; Scognamiglio, Marianna; O'Donovan, Peter; Campo, Rudi; De Wilde, Rudy L.
Abstract: Objective: The purpose of the present review is to provide a survey of the various measures of preventing adhesions used in hysteroscopic surgery. Study Design: A systematic computerized literature search was conducted to provide a survey of the various measures used in hysteroscopic surgery to prevent adhesions. Finally, 29 studies were included in the analysis, showing a wide variety of methods and agents advocated in international literature. They are explained in various sections, based on the IUA prevention approach adopted (surgical technique, early second-look hysteroscopy, barrier method, pharmacological therapy). Results: The results of our review show that (i) use of surgical techniques which reduce the use of electrosurgery should be preferred whenever possible (Level of evidence: 4); (ii) an early second-look hysteroscopy would appear to be an effective preventive, as well as therapeutic, strategy regarding IUA but studies on the topic are too few for relevant evidence; (iii) barriers methods are the most widely used and, among these, gel barriers have been proven to have a significant clinical effect on IUA prevention, because of higher adhesiveness and prolonged residence time on the injured surface (Level of evidence: 1b); (iv) the role of hormonal and antibiotic therapy in the prevention of post-operative IUA is difficult to evaluate as it has been used in association with other prevention strategies in most studies included in our review. Conclusions: Robust and high quality randomized trials to assess the effectiveness of different anti-adhesion therapies are still needed before one or more of these strategies may be strongly recommended for improving clinical outcomes in women treated by operative hysteroscopy.